Spinal anesthesia for laparoscopic cholecystectomy: Thoracic vs. Lumbar Technique - Imbelloni, Luiz [UNESP] (2014)
Aims: In our group, after a study showing that spinal anesthesia is safe when compared with general anesthesia, spinal anesthesia has been the technique of choice for this procedure. This is a prospective study with all patients undergoing LC under spinal anesthesia in our department since 2007. Settings and Design: Prospective observational. Materials and Methods: From 2007 to 2011, 369 patients with symptoms of colelithiasis, laparoscopic cholecystectomy were operated under spinal anesthesia with pneumoperitoneum and low pressure CO2. We compared 15 mg of hyperbaric bupivacaine and lumbar puncture with 10 or 7.5 mg of hyperbaric bupivacaine thoracic puncture, all with 25 μg fentanyl until the sensory level reached T3. Intraoperative parameters, post-operative pain, complications, recovery, patient satisfaction, and cost were compared between both groups. Statistical Analysis Used: Means were compared by ANOVA or Kruskal-Wallis test, the percentages of the Chi-square test or Fisher's exact test when appropriate. Time of motor and sensory block in spinal anesthesia group was compared by paired t test or Mann-Whitney test. Differences were considered significant when P ≤ 0.05, and for comparisons of mean pain visual scale, we employed the Bonferroni correction applied to be considered significant only with P ≤ 0.0125 Results: All procedures were completed under spinal anesthesia. The use of lidocaine 1% was successful in the prevention of shoulder pain in 329 (89%) patients. There were significant differences in time to reach T3, obtaining 15 mg > 10 mg = 7.5 mg. There is a positive correlation between the dose and the incidence of hypotension. The lowest doses gave a decrease of 52.2% in the incidence of hypotension. There was a positive correlation between the dose and duration of sensory and motor block. Sensory block was almost twice the motor block at all doses. With low doses, 60% of patients went from table to stretcher. Satisfaction occurred in 99% of patients. Conclusions: Laparoscopic cholecystectomy can be performed successfully under spinal anesthesia with low-pressure pneumoperitoneum of CO2. The use of thoracic puncture and low doses of hyperbaric bupivacaine provided better hemodynamic stability, less hypotension, and shorter duration of sensory and motor blockade than lumbar spinal anesthesia with conventional doses.